Technical Possibilities of Reducing the Sound Pressure Level Emitted into the Environment by a Power Transformer - BORUCKI, Sebastian; BOCZAR, Tomasz; CICHON, Andrzej (Archives of Acoustics, 2011)
The subject presented in this paper refers to measurements and assessment of the corrected sound pressure level values (noise) occurring around a medium-power transformer. The paper presents the values of noise accompanying the operation of the power object before and after its modernization, which consisted in repeated core pressing and replacement of the cooling system. The main aim of the research work was the assessment of the influence of the repair work on the noise level emitted into the environment.